Analisis Minat Membaca Peserta Didik Pada Pembelajaran IPS SMP Kelas 7 di Pontianak - Nasari, Aris; Aminuyati, Aminuyati; Wiyono, Hadi; Buwono, Sri; Karolina, Venny (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the interest in reading of students in social studies learning in grade 7 junior high school in Pontianak city and the teacher's efforts to increase students' interest in reading in social studies learning in grade 7 in Pontianak. This research is a descriptive qualitative research with research subjects namely 1 social studies teacher, 1 library officer, and 5 students. Data collection techniques using observation, interviews and documentation. The data collection tools are observation guides, interview guides and documentation using cameras. Data validity testing techniques in this study using triangulation of sources, techniques and time. The results of this study indicate that students' interest in reading in social studies learning is seen from the factor of availability of time to read, the habit of reading, the availability of books to read, the role of the library, and the condition of books in the school reading corner. Teachers' efforts to increase students' interest in reading in social studies learning such as teachers directing students to read social studies books for 15 minutes before learning, teachers provide motivation to students to read, and teachers utilize facilities and infrastructure by providing additional social studies material in the form of files.